A luggage case beverage placement rack and preparation method thereof
By using carbon fiber, PA fiber, asbestos fiber composite fiber and lignin modified rubber in luggage drinking racks, the existing luggage drinks are easily damaged, and higher load -bearing and impact resistance has been achieved. Improved the experience.
Patent Information
- Application Number
- CN202410770545.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The existing suitcase and beverage placing rack is easily damaged during use and cannot be replaced separately, which affects the consumer's experience.
Carbon fiber, PA fiber, and asbestos fiber are used as composite fibers, and lignin modified rubber is used as a tougin agent. The rubber is modified by amino lignin to improve the load and impact capacity of the luggage drinking rack.
It significantly improves the load -bearing intensity and impact strength of the luggage beverage. It extends its service life and enhances consumer experience.
Smart Images

Figure BDA0004893945950000081 
Figure BDA0004893945950000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer material technology, and in particular to a luggage case beverage placement rack and a preparation method thereof. Background Art
[0002] Nowadays, when people are on business trips or traveling, in order to carry the necessary luggage, they usually choose to use a suitcase to carry. However, due to the large or heavy luggage, it is usually inconvenient to carry beverages such as coffee and juice. Therefore, in order to solve the problem that it is inconvenient to hold a cup or a beverage in the hand due to the large or heavy luggage when people travel, a luggage beverage placement rack structure is added to the existing luggage.
[0003] A luggage case beverage rack generally consists of a guard frame and a support plate installed on a connecting plate. The cup is placed from top to bottom from the guard frame and supported by the bottom through the support plate, so that the cup can be stably placed in the cup. In order to prevent the beverage rack from protruding out when not in use, the guard frame and the support plate can be set to a foldable structure. When the cup holder is not in use, the guard frame and the support plate can be folded and embedded on the side wall of the luggage case.
[0004] However, in daily use, the beverage rack is easily damaged due to the impact of the suitcase tipping over, collision or its own low load-bearing capacity, and the damaged beverage rack cannot be replaced individually, which affects the consumer's experience of use and limits the development of this type of suitcase. Summary of the invention
[0005] In order to improve the load-bearing capacity and drop resistance of a luggage case beverage rack, the present application provides a luggage case beverage rack and a preparation method thereof.
[0006] The present application provides a luggage beverage rack, which adopts the following technical solution:
[0007] A luggage case beverage placement rack and a preparation method thereof, comprising the following raw materials in parts by weight: 30-60 parts of PP resin, 10-40 parts of ABS resin, 10-20 parts of composite fibers, 5-15 parts of modified rubber toughening agents, 1-3 parts of antioxidants, 1-3 parts of dispersants, and 3-6 parts of compatibilizers; the modified rubber toughening agent is lignin-modified rubber; the composite fibers include carbon fibers, PA fibers, and asbestos fibers, and the weight ratio of the three is 1:(0.5-1.5):(0.2-0.9).
[0008] Preferably, the luggage suitcase beverage rack comprises the following raw materials in parts by weight: 45 parts of PP resin, 25 parts of ABS resin, 15 parts of composite fibers, 10 parts of modified rubber toughening agent, 2 parts of antioxidant, 2 parts of dispersant, and 4.5 parts of compatibilizer; the modified rubber toughening agent is lignin modified rubber; the composite fibers include carbon fibers, PA fibers, and asbestos fibers, and the weight ratio of the three is 1:1:0.6.
[0009] By adopting the above technical scheme, by using carbon fiber, PA fiber and asbestos fiber as composite fiber, carbon fiber is light in weight, high in strength, high in modulus, has excellent mechanical properties and chemical stability, and can effectively enhance the strength and toughness of resin; asbestos fiber has high temperature resistance, chemical corrosion resistance and heat insulation properties, and can effectively enhance the resin; PA fiber is a high-strength, high-modulus fiber with excellent mechanical properties and wear resistance, and can also effectively enhance the strength of resin; in addition, lignin-modified rubber is used as a toughening agent, and the rubber is modified by amino lignin, which effectively solves the disadvantage that the strength of the resin will be reduced after the toughness of the resin is increased, and the strength and hardness of the rubber are significantly improved, thereby improving its wear resistance and fatigue resistance, and effectively improving the load-bearing strength and impact strength of the luggage compartment beverage placement rack.
[0010] Preferably, the lignin modified rubber is prepared from the following raw materials in parts by weight: 5-12 parts of amino lignin, 150-180 parts of rubber, 7-10 parts of methacrylate, 4-11 parts of azobisisobutyronitrile, 3-8 parts of methyltrimethoxysilane, and 3-4 parts of 2,6-di-tert-butyl-p-cresol.
[0011] By adopting the above technical solution, the rubber is modified by amino lignin, which can significantly improve the strength and hardness of the rubber, thereby improving the wear resistance and fatigue resistance of the luggage compartment beverage rack; in addition, lignin can improve the flexibility and elasticity of the rubber, so that it can adapt to different ambient temperatures, which allows the luggage compartment beverage rack to maintain good performance under different temperature conditions.
[0012] Preferably, the rubber is one of natural rubber, styrene-butadiene rubber, butadiene rubber and chloroprene rubber.
[0013] Preferably, the amino lignin is prepared from the following raw materials in parts by weight: 40-60 parts of lignin, 20-30 parts of hydrochloric acid, 20-30 parts of amino functionalizing agent, 15-25 parts of cross-linking agent, and 120-180 parts of water.
[0014] By adopting the above technical solution, the reaction activity of lignin can be increased by performing amination modification on lignin, promoting its bonding with rubber, and effectively obtaining lignin-modified rubber; and the amination-modified lignin is more conducive to improving the strength and hardness of the rubber.
[0015] Preferably, the amino functionalizing agent is one of ammonia water, triethylamine and dimethylamine.
[0016] The present application provides a luggage beverage rack, which adopts the following technical solution:
[0017] A method for preparing a luggage beverage rack comprises the following steps:
[0018] S1. Mix 30-60 parts of PP resin, 10-40 parts of ABS resin, 5-15 parts of modified rubber toughening agent, and 1-3 parts of dispersant, and stir and disperse them efficiently; then add 10-20 parts of composite fiber, and stir and disperse them efficiently; finally, add 1-3 parts of antioxidant and 3-6 parts of compatibilizer, stir and disperse them, and obtain a mixture;
[0019] S2. The mixture is fed into an extruder for extrusion granulation; and then formed in a mold, cooled, trimmed, and shaped to obtain a luggage compartment beverage rack;
[0020] The modified rubber toughening agent is lignin modified rubber; the composite fiber includes carbon fiber, PA fiber and asbestos fiber, and the weight ratio of the three is 1: (0.5-1.5): (0.2-0.9).
[0021] Preferably, the method for preparing the lignin-modified rubber comprises the following steps:
[0022] Add 5-12 parts of amino lignin and 150-180 parts of rubber into a mixer and mix evenly, add 3-4 parts of antioxidant and mix evenly, add appropriate amount of water, heat and stir for 0.5-2h, add 7-10 parts of methacrylate, continue stirring for 0.5-1h, add 4-11 parts of azobisisobutyronitrile and 3-8 parts of methyltrimethoxysilane, heat and stir to react for 1-3h, cool to room temperature after the reaction is completed, and ripen to obtain lignin modified rubber.
[0023] Preferably, the method for preparing the amino lignin comprises the following steps:
[0024] Add 40-60 parts of lignin to 120-180 parts of water, add 20-30 parts of hydrochloric acid, heat to 50-60°C, and let stand for 8-12 hours; add 20-30 parts of amino functionalization reagent, heat to 90-100°C, and keep warm for reaction for 1-3 hours; add 15-25 parts of cross-linking agent, keep warm for reaction for 2-4 hours, and after the reaction is completed, adjust the pH of the reaction solution to neutral to obtain amino lignin.
[0025] In summary, the present application includes at least one of the following beneficial technical effects:
[0026] 1. By adopting the above technical scheme, carbon fiber, PA fiber and asbestos fiber are used as composite fibers. Carbon fiber is light, high in strength, high in modulus, and has excellent mechanical properties and chemical stability, which can effectively enhance the strength and toughness of the resin; asbestos fiber has high temperature resistance, chemical corrosion resistance and heat insulation properties, which can effectively enhance the resin; PA fiber is a high-strength, high-modulus fiber with excellent mechanical properties and wear resistance, which can also effectively enhance the strength of the resin; in addition, lignin-modified rubber is used as a toughening agent, and the rubber is modified by amino lignin, which effectively solves the disadvantage that the strength of the resin will be reduced after the toughness of the resin is increased, and the strength and hardness of the rubber are significantly improved, thereby improving its wear resistance and fatigue resistance, and effectively improving the load-bearing strength and impact resistance of the luggage compartment beverage rack;
[0027] 2. By adopting the above technical solution, the rubber is modified by amino lignin, which can significantly improve the strength and hardness of the rubber, thereby improving the wear resistance and fatigue resistance of the luggage compartment beverage rack; in addition, lignin can improve the flexibility and elasticity of the rubber, so that it can adapt to different ambient temperatures, which enables the luggage compartment beverage rack to maintain good performance under different temperature conditions;
[0028] 3. By adopting the above technical scheme, by performing amination modification on lignin, the reaction activity of lignin can be increased, and its bonding with rubber can be promoted, so as to effectively obtain lignin-modified rubber; and the amination-modified lignin is more conducive to improving the strength and hardness of the rubber. DETAILED DESCRIPTION
[0029] The present application is further described in detail below with reference to the embodiments.
[0030] Preparation Example
[0031] Preparation Example 1
[0032] S1. Add 40g of lignin to 120g of water, mix and stir evenly, add 20g of 30% hydrochloric acid, heat to 50°C, and let stand for 8h; add 20g of amino functional reagent ammonia water, heat to 90°C, and keep warm for 3h; add 15g of ethylenediamine, keep warm for 2h, and after the reaction, adjust the pH of the reaction solution to neutral to obtain amino lignin;
[0033] S2. Add 5g of amino lignin obtained from S1 and 150g of natural rubber into a mixer and mix evenly, add 3g of 2,6-di-tert-butyl-p-cresol and mix evenly, add an appropriate amount of water, heat and stir for 0.5h, add 7g of methyl acrylate, and continue stirring for 0.5h; add 3g of methyltrimethoxysilane to a solution obtained by mixing deionized water and anhydrous ethanol in a ratio of 9:1, stir well for hydrolysis, then add into the mixer, add 4g of azobisisobutyronitrile, heat and stir for reaction for 1h, cool to room temperature after the reaction is completed, and ripen to obtain lignin modified rubber.
[0034] Preparation Example 2
[0035] S1. Add 40g of lignin to 160g of water, mix and stir evenly, add 25g of 30% hydrochloric acid, heat to 55°C, and let stand for 10h; add 20g of amino functionalization reagent triethylamine ammonia water, heat to 95°C, and keep warm for 2h; add 20g of ethylenediamine, keep warm for 3h, and after the reaction is completed, adjust the pH of the reaction solution to neutral to obtain amino lignin;
[0036] S2. Add 5g of amino lignin obtained from S1 and 165g of styrene-butadiene rubber into a mixer and mix evenly, add 3.5g of 2,6-di-tert-butyl-p-cresol and mix evenly, add an appropriate amount of water, heat and stir for 1.5h, add 8.5g of methyl methacrylate, and continue stirring for 0.75h; add 5g of methyltrimethoxysilane to a solution obtained by mixing deionized water and anhydrous ethanol in a ratio of 9:1, stir well for hydrolysis, then add into the mixer, add 7g of azobisisobutyronitrile, heat and stir for reaction for 2h, cool to room temperature after the reaction is completed, and ripen to obtain lignin-modified rubber.
[0037] Preparation Example 3
[0038] S1. Add 40g of lignin to 180g of water, mix and stir evenly, add 30g of 30% hydrochloric acid, heat to 60°C, and let stand for 12h; add 20g of amino functionalization reagent dimethylamine, heat to 100°C, and keep warm for 1h; add 25g of ethylenediamine, keep warm for 4h, and after the reaction is completed, adjust the pH of the reaction solution to neutral to obtain amino lignin;
[0039] S2. Add 5g of amino lignin obtained from S1 and 180g of butadiene rubber into a mixer and mix evenly, add 4g of 2,6-di-tert-butyl-p-cresol and mix evenly, add an appropriate amount of water, heat and stir for 2h, add 10g of methyl methacrylate, and continue stirring for 0.5h; add 8g of methyltrimethoxysilane to a solution obtained by mixing deionized water and anhydrous ethanol in a ratio of 9:1, stir well for hydrolysis, then add into the mixer, add 11g of azobisisobutyronitrile, heat and stir for 3h, cool to room temperature after the reaction is completed, and ripen to obtain lignin modified rubber.
[0040] Preparation Example 4
[0041] The difference between Preparation Example 4 and Preparation Example 1 is that the mass of lignin used in S1 of Preparation Example 4 is 50 g.
[0042] Preparation Example 5
[0043] The difference between Preparation Example 5 and Preparation Example 1 is that the mass of lignin used in S1 of Preparation Example 5 is 60 g.
[0044] Preparation Example 6
[0045] The difference between Preparation Example 6 and Preparation Example 1 is that the mass of lignin used in S1 of Preparation Example 6 is 30 g.
[0046] Preparation Example 7
[0047] The difference between Preparation Example 7 and Preparation Example 1 is that the mass of lignin used in S1 of Preparation Example 7 is 70 g.
[0048] Preparation Example 8
[0049] The difference between Preparation Example 8 and Preparation Example 1 is that the mass of the amino functionalizing agent dimethylamine used in S1 of Preparation Example 8 is 25 g.
[0050] Preparation Example 9
[0051] The difference between Preparation Example 9 and Preparation Example 1 is that the mass of the amino functionalizing agent dimethylamine used in S1 of Preparation Example 9 is 30 g.
[0052] Preparation Example 10
[0053] The difference between Preparation Example 10 and Preparation Example 1 is that the mass of the amino functionalizing agent dimethylamine used in S1 of Preparation Example 10 is 15 g.
[0054] Preparation Example 11
[0055] The difference between Preparation Example 11 and Preparation Example 1 is that the mass of the amino functionalizing agent dimethylamine used in S1 of Preparation Example 11 is 35 g.
[0056] Preparation Example 12
[0057] The difference between Preparation Example 12 and Preparation Example 1 is that the mass of the amino lignin obtained from S1 used in S2 of Preparation Example 12 is 8.5 g.
[0058] Preparation Example 13
[0059] The difference between Preparation Example 13 and Preparation Example 1 is that the mass of the amino lignin obtained from S1 used in S2 of Preparation Example 13 is 12 g.
[0060] Preparation Example 14
[0061] The difference between Preparation Example 14 and Preparation Example 1 is that the mass of the aminolated lignin obtained from S1 used in S2 of Preparation Example 14 is 2 g.
[0062] Preparation Example 15
[0063] The difference between Preparation Example 15 and Preparation Example 1 is that the mass of the aminolated lignin obtained from S1 used in S2 of Preparation Example 15 is 15 g.
[0064] Example
[0065] Example 1
[0066] S1. 30 g PP resin, 10 g ABS resin, 5 g of the modified rubber toughening agent obtained in Preparation Example 1, and 1 g of stearic acid dispersant were mixed and efficiently stirred and dispersed for 15 min; 10 g of composite fiber was then added and efficiently stirred again for 15 min; finally, 1 g of antioxidant 2,6-di-tert-butyl-p-cresol and 3 g of compatibilizer POE were added and stirred for 30 min to obtain a mixture;
[0067] S2. The mixed material is put into an extruder for extrusion granulation, the extrusion temperature is 230°C, the screw speed is 450rpm, and the pellets are obtained; then the pellets are injected into a molding mold by a plastic injection machine, the barrel temperature is 245°C, the machine temperature is 30°C, the injection pressure is 11MPa, and the injection time is 4s; after demolding, cooling, trimming, shaping and other processes, a luggage compartment beverage placement rack is obtained;
[0068] The composite fiber in this embodiment includes carbon fiber, PA fiber and asbestos fiber, and the weight ratio of the three is 1:0.5:0.2.
[0069] Example 2
[0070] S1. 45g PP resin, 25g ABS resin, 10g modified rubber toughening agent obtained in Preparation Example 1, 2g dispersant stearic acid were mixed and efficiently stirred and dispersed for 25min; then 15g composite fiber was added and efficiently stirred again for 25min; finally, 2g antioxidant 2,6-di-tert-butyl-p-cresol and 4.5g compatibilizer POE were added and stirred for 45min to obtain a mixture;
[0071] S2. The mixed material is put into an extruder for extrusion granulation, the extrusion temperature is 200°C, the screw speed is 400rpm, and the pellets are obtained; then the pellets are injected into a molding mold by a plastic injection machine, the barrel temperature is 250°C, the machine temperature is 35°C, the injection pressure is 12MPa, and the injection time is 5s; after demolding, cooling, trimming, shaping and other processes, a luggage compartment beverage placement rack is obtained;
[0072] The composite fiber in this embodiment includes carbon fiber, PA fiber and asbestos fiber, and the weight ratio of the three is 1:1:0.6.
[0073] Example 3
[0074] S1. 60g PP resin, 40g ABS resin, 15g modified rubber toughening agent obtained in Preparation Example 1, 3g dispersant stearic acid were mixed and efficiently stirred and dispersed for 15min; then 20g composite fiber was added and efficiently stirred again for 15min; finally, 3g antioxidant 2,6-di-tert-butyl-p-cresol and 6g compatibilizer POE were added and stirred for 30min to obtain a mixture;
[0075] S2. The mixed material is put into an extruder for extrusion granulation, the extrusion temperature is 250°C, the screw speed is 460rpm, and the pellets are obtained; then the pellets are injected into a molding mold by a plastic injection machine, the barrel temperature is 255°C, the tool temperature is 33°C, the injection pressure is 12.5MPa, and the injection time is 4s; after demolding, cooling, trimming, shaping and other processes, a luggage compartment beverage placement rack is obtained;
[0076] The composite fiber in this embodiment includes carbon fiber, PA fiber and asbestos fiber, and the weight ratio of the three is 1:1.5:0.9.
[0077] Example 4
[0078] The difference between Example 4 and Example 1 is that the modified rubber toughening agent used in Example 4 comes from Preparation Example 2.
[0079] Example 5
[0080] The difference between Example 5 and Example 1 is that the modified rubber toughening agent used in Example 5 comes from Preparation Example 3.
[0081] Example 6
[0082] The difference between Example 6 and Example 1 is that the modified rubber toughening agent used in Example 6 comes from Preparation Example 4.
[0083] Example 7
[0084] The difference between Example 7 and Example 1 is that the modified rubber toughening agent used in Example 7 comes from Preparation Example 5.
[0085] Example 8
[0086] The difference between Example 8 and Example 1 is that the modified rubber toughening agent used in Example 8 comes from Preparation Example 6.
[0087] Example 9
[0088] The difference between Example 9 and Example 1 is that the modified rubber toughening agent used in Example 9 comes from Preparation Example 7.
[0089] Example 10
[0090] The difference between Example 10 and Example 1 is that the modified rubber toughening agent used in Example 10 comes from Preparation Example 8.
[0091] Embodiment 11
[0092] The difference between Example 11 and Example 1 is that the modified rubber toughening agent used in Example 11 comes from Preparation Example 9.
[0093] Example 12
[0094] The difference between Example 12 and Example 1 is that the modified rubber toughening agent used in Example 12 comes from Preparation Example 10.
[0095] Embodiment 13
[0096] The difference between Example 13 and Example 1 is that the modified rubber toughening agent used in Example 13 comes from Preparation Example 11.
[0097] Embodiment 14
[0098] The difference between Example 14 and Example 1 is that the modified rubber toughening agent used in Example 14 comes from Preparation Example 12.
[0099] Embodiment 15
[0100] The difference between Example 15 and Example 1 is that the modified rubber toughening agent used in Example 15 comes from Preparation Example 13.
[0101] Example 16
[0102] The difference between Example 16 and Example 1 is that the modified rubber toughening agent used in Example 16 comes from Preparation Example 14.
[0103] Embodiment 17
[0104] The difference between Example 17 and Example 1 is that the modified rubber toughening agent used in Example 17 comes from Preparation Example 15.
[0105] Comparative Example
[0106] Comparative Example 1
[0107] The difference between Comparative Example 1 and Example 1 is that the toughening agent used in Comparative Example 1 is unmodified natural rubber with a mass of 5 g.
[0108] Comparative Example 2
[0109] The difference between Comparative Example 2 and Example 1 is that the toughening agent used in Comparative Example 2 is unmodified styrene-butadiene rubber with a mass of 5 g.
[0110] Comparative Example 3
[0111] The difference between Comparative Example 3 and Example 1 is that the toughening agent used in Comparative Example 3 is unmodified butadiene rubber with a mass of 5 g.
[0112] Comparative Example 4
[0113] The difference between Comparative Example 4 and Example 1 is that the mass of the composite fiber used in Comparative Example 4 is 10 g, wherein the composite fiber includes carbon fiber, PA fiber and asbestos fiber, and the weight ratio of the three is 1:0.3:0.1.
[0114] Comparative Example 5
[0115] The difference between Comparative Example 5 and Example 1 is that the mass of the composite fiber used in Comparative Example 5 is 10 g, wherein the composite fiber includes carbon fiber, PA fiber and asbestos fiber, and the weight ratio of the three is 1:1.8:1.2.
[0116] Performance testing
[0117] 1. The bearing strength of the luggage beverage racks obtained in Examples 1-17 and Comparative Examples 1-5 was measured using GB / T 14484-2008 “Determination of bearing strength of plastics”. The results are shown in Table 1.
[0118] 2. With reference to GB / T 1843-2008 “Determination of Izod Impact Strength of Plastics”, the impact strength of the luggage beverage racks obtained in Examples 1-17 and Comparative Examples 1-5 was measured. The results are shown in Table 1.
[0119] The specific test results are as follows:
[0120] Table 1 Performance test results
[0121]
[0122]
[0123] It can be seen from the test results of Examples 1-3 and Comparative Examples 4 and 5 that the components of the luggage case beverage rack provided in the present application and the preparation method thereof are conducive to obtaining a luggage case beverage rack with high bearing strength and impact resistance; it indicates that the luggage case beverage rack provided in the present application has good bearing capacity and strong drop resistance; and when the raw materials of the luggage case beverage rack are 45 parts of PP resin, 25 parts of ABS resin, 15 parts of composite fibers, 10 parts of modified rubber toughening agent, 2 parts of antioxidant, 2 parts of dispersant, and 4.5 parts of compatibilizer; the modified rubber toughening agent is lignin modified rubber; the composite fibers include carbon fiber, PA fiber, and asbestos fiber, and the weight ratio of the three is 1:1:0.6, the bearing strength and impact resistance of the obtained luggage case beverage rack are the best.
[0124] It can be seen from the test results of Examples 1, 4, 5 and Comparative Examples 1-3 that the component of a modified rubber toughening agent lignin modified rubber and its preparation method provided in the present application can effectively improve the bearing strength and impact strength of the luggage case beverage rack; however, when unmodified rubber is used, the bearing strength and impact strength of the obtained luggage case beverage rack are significantly reduced.
[0125] It can be seen from the test results of Examples 1, 6, 7, 8, and 9 that when the weight of the raw material lignin used in the preparation of the amino lignin in the present application increases, when the lignin-modified rubber prepared from the amino lignin is used as the raw material for the luggage beverage rack, the bearing strength and impact strength of the obtained luggage beverage rack both show a trend of first increasing and then decreasing, so the preferred weight of lignin is 40-60 parts.
[0126] It can be seen from the test results of Examples 1, 10, 11, 12, and 13 that when the weight of the raw material of the amino functionalizing agent used in the preparation of the amino lignin in the present application increases, when the lignin-modified rubber prepared from the amino lignin is used as the raw material of the luggage beverage rack, the bearing strength and impact strength of the obtained luggage beverage rack both show a trend of first increasing and then decreasing. Therefore, the preferred weight of the amino functionalizing agent is 20-30 parts.
[0127] It can be seen from the test results of Examples 1, 14, 15, 16, and 17 that when the weight percentage of the raw material of the amino lignin used in the preparation of the lignin-modified rubber in the present application increases, when the obtained lignin-modified rubber is used as the raw material for a luggage beverage rack, the bearing strength and impact strength of the obtained luggage beverage rack both show a trend of first increasing and then decreasing. Therefore, the preferred weight percentage of the amino lignin is 5-12 parts.
[0128] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A luggage beverage rack, characterized in that: The invention comprises the following raw materials in parts by weight: 30-60 parts of PP resin, 10-40 parts of ABS resin, 10-20 parts of composite fiber, 5-15 parts of modified rubber toughening agent, 1-3 parts of antioxidant, 1-3 parts of dispersant, and 3-6 parts of compatibilizer; the modified rubber toughening agent is lignin modified rubber; the composite fiber comprises carbon fiber, PA fiber, and asbestos fiber, and the weight ratio of the three is 1: (0.5-1.5): (0.2-0.9); The lignin modified rubber is prepared from the following raw materials in parts by weight: 5-12 parts of amino lignin, 150-180 parts of rubber, 7-10 parts of methacrylate, 4-11 parts of azobisisobutyronitrile, 3-8 parts of methyltrimethoxysilane, and 3-4 parts of 2,6-di-tert-butyl-p-cresol; The amino lignin is prepared from the following raw materials in parts by weight: 40-60 parts of lignin, 20-30 parts of hydrochloric acid, 20-30 parts of amino functionalization reagent, 15-25 parts of cross-linking agent, and 120-180 parts of water; The preparation method of the lignin modified rubber comprises the following steps: Add 5-12 parts of amino lignin and 150-180 parts of rubber into a mixer and mix evenly, add 3-4 parts of 2,6-di-tert-butyl-p-cresol and mix evenly, add an appropriate amount of water, heat and stir for 0.5-2h, add 7-10 parts of methacrylate, continue stirring for 0.5-1h, add 4-11 parts of azobisisobutyronitrile and 3-8 parts of methyltrimethoxysilane, heat and stir to react for 1-3h, cool to room temperature after the reaction is completed, and ripen to obtain lignin modified rubber; The preparation method of the amino lignin comprises the following steps: Add 40-60 parts of lignin to 120-180 parts of water, add 20-30 parts of hydrochloric acid, heat to 50-60°C, and let stand for 8-12 hours; add 20-30 parts of amino functionalization reagent, heat to 90-100°C, and keep warm for reaction for 1-3 hours; add 15-25 parts of cross-linking agent, keep warm for reaction for 2-4 hours, and after the reaction is completed, adjust the pH of the reaction solution to neutral to obtain amino lignin.
2. The luggage case beverage rack according to claim 1, characterized in that: The luggage suitcase beverage storage rack includes the following raw materials in parts by weight: 45 parts of PP resin, 25 parts of ABS resin, 15 parts of composite fiber, 10 parts of modified rubber toughening agent, 2 parts of antioxidant, 2 parts of dispersant, and 4.5 parts of compatibilizer; the modified rubber toughening agent is lignin modified rubber; the composite fiber includes carbon fiber, PA fiber, and asbestos fiber, and the weight ratio of the three is 1:1:0.
6.
3. The luggage beverage rack according to claim 1, characterized in that: The rubber is one of natural rubber, styrene-butadiene rubber, butadiene rubber and chloroprene rubber.
4. The luggage case beverage rack according to claim 1, characterized in that: The amino functionalization reagent is one of ammonia water, triethylamine and dimethylamine.
5. A method for preparing a luggage beverage rack according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Mix 30-60 parts of PP resin, 10-40 parts of ABS resin, 5-15 parts of modified rubber toughening agent, and 1-3 parts of dispersant, and stir and disperse them efficiently; then add 10-20 parts of composite fiber, and stir and disperse them efficiently; finally, add 1-3 parts of antioxidant and 3-6 parts of compatibilizer, stir and disperse them, and obtain a mixture; S2. The mixture is fed into an extruder for extrusion granulation; and then formed in a mold, cooled, trimmed, and shaped to obtain a luggage compartment beverage rack; The modified rubber toughening agent is lignin modified rubber; the composite fiber includes carbon fiber, PA fiber and asbestos fiber, and the weight ratio of the three is 1: (0.5-1.5): (0.2-0.9).
Citation Information
Patent Citations
Fiber reinforcement type lightweight composite material with layer structures for automobiles
CN106985484A
Modified lignin compound, high-toughness lignin-based polymer composite material, preparation method and application
CN113201149A